Evaluation of the Effects of Interfering Factors on the Bacterial Endotoxin Testing of Radiopharmaceuticals - Jun Young PARK (Korean Journal of Clinical Laboratory Science, 2024)
The endotoxin test is based on the reaction between Limulus Amebocyte Lysate (LAL) and the lipopolysaccharides of Gram-negative bacteria. In this study, we sought to identify factors that interfere with the LAL testing of radiopharmaceuticals and evaluated acceptable ranges. A gel-clot LAL test and a chromogenic LAL test were used as endotoxin tests. We compared the performances of the EndosafeⓇ LAL and recombinant EndosafeⓇ Recombinant Cascade Reagent (rCR) cartridges for the chromogenic test. The factors that interfered with 68Ga-DOTATOC injection were pH, 4-(2-hydroxyethyl) piperazine-1-ethanesulfonic acid (HEPES) buffer, and organic solvents, especially ethanol. However, interference by these factors was overcome by diluting the 68Ga-DOTATOC injection tenfold. In addition, no interference was observed at pH values between 4 and 8, at a HEPES concentration of 2,000 μg/mL, or an ethanol concentration of <1%. Furthermore, results showed that interfering factors had similar effects on the performances of the EndosafeⓇ LAL and EndosafeⓇ rCR cartridges. The results of this study are expected to be useful for evaluating factors that interfere with the endotoxin testing of new radiopharmaceuticals.